Biological parameters and respiration data of Pyrosoma atlanticum from DESAFIO cruise (January-March 2023) in Northeast Atlantic Ocean - Airam Nauzet Sarmiento-Lezcano; María Couret; Javier Díaz-Pérez; Ainhoa Bernal; Vanesa Raya; Martín Pla; Nicolás Larrumbide-Zúñiga; Arturo Castellón; Santiago Hernández-León (PANGAEA, 2025)
The values of carbon flux were measured in Pyrosoma atlanticum sampled during the DESAFIO cruise (North Atlantic, January-March 2023). This dataset contains the values of colony length, body width, body area, wet weight (two measurements), dry weight, specific ETS activity, respiration (three methods), and specific respiration (two models), analyzed along a transect from the north of the Azores Islands to the African coast, covering mainly the subtropical zone of the Atlantic Ocean. P. atlanticum specimens were collected using a "Mesopelagos" net (5 exttimes 7 m mouth opening, 58 m total length) equipped with graded-mesh netting (starting with 30 mm and ending with 4 mm) and a multi-sampler for collecting samples from 7 different depth layers (Castellón and Olivar, 2023, doi:10.3390/jmse11010072), and the Multiple Opening/Closing Net and Environmental Sensing System (MOCNESS-1 m^2) zooplankton net (Wiebe et al., 1985, doi:10.1007/BF00397811) with a 0.2 mm mesh size and several nets for sampling from 8 different depth layers. The Mesopelagos catches were sorted out and identified on board to the lowest possible taxon, and specimens selected for Electron Transfer System (ETS) analyses were immediately frozen in liquid nitrogen for later laboratory analysis. MOCNESS samples were preserved in 5% buffered formalin, and specimens were sorted later in the laboratory. Two approaches were used to estimate pyrosome active flux: (1) the enzymatic activity of the electron transfer system (ETS), and (2) a specific respiration equation (RC, Al-Mutairi and Landry (2001, doi:10.1016/S0967-0645(00)00174-0)) for P. atlanticum in the meso- and bathypelagic zones of the ocean. Colony length, body width, body area, wet weight, dry weight, specific ETS activity, respiration, and specific respiration are given by layer.